2021
DOI: 10.3390/atmos12081068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PM2.5 on Chronic Airway Diseases: A Review of Research Progress

Abstract: The adverse effects of polluted air on human health have been increasingly appreciated worldwide. It is estimated that outdoor air pollution is associated with the death of 4.2 million people globally each year. Accumulating epidemiological studies indicate that exposure to ambient fine particulate matter (PM2.5), one of the important air pollutants, significantly contributes to respiratory mortality and morbidity. PM2.5 causes lung damage mainly by inducing inflammatory response and oxidative stress. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…This study also confirmed that the ingestion of the HY2782 complex increased the levels of antioxidant-related factors, such as Nrf2, SOD1, and CAT, which inhibit ROS production. In a previous study, diesel PM2.5 significantly altered the structure and composition of mice gut microbiota, in which a decrease in Lactobacillus abundance could suppress butyrate production and thus could exacerbate the immune defense of the gut ( Liu et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study also confirmed that the ingestion of the HY2782 complex increased the levels of antioxidant-related factors, such as Nrf2, SOD1, and CAT, which inhibit ROS production. In a previous study, diesel PM2.5 significantly altered the structure and composition of mice gut microbiota, in which a decrease in Lactobacillus abundance could suppress butyrate production and thus could exacerbate the immune defense of the gut ( Liu et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity caused by PM2.5 is a combined effect of particles and toxic pollutants adsorbed to the particles, such as biological components (bacteria, fungi, and viruses and their metabolites), volatile organic compounds [benzene, toluene, and polycyclic aromatic hydrocarbons (PAHs)], and heavy metals ( Shen et al, 2018 ). PM2.5 is one of the most harmful pollutants to human health because it can even penetrate the alveoli and bronchi and cause airway inflammation and respiratory diseases ( Liu et al, 2021a ). Inhalation of PM2.5 is associated with many respiratory tract diseases, such as allergic rhinitis, airway hyperresponsiveness (AHR), asthma, and chronic obstructive pulmonary disease (COPD; Li and Liu, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Health Organization (WHO) estimated 7 million people die per year from outdoor and indoor air pollution [ 1 ]. In particular, the micro-size of PM with an aerodynamic diameter of less than 2.5 µm (PM 2.5 ), which can penetrate deeply into alveoli, has been associated with several diseases, such as cancer [ 2 ], respiratory illnesses [ 3 , 4 ], and cardiovascular diseases [ 5 ]. To protect vulnerable people from this harmful situation, the demand and usage of face masks and air filters significantly increased worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, the air pollution consequences in the environment and health have been the subject of deep researches [2][3][4], including the relation between air pollution and human health [5][6][7][8] and, specifically, the study of particulate matter (PM) impacts on the respiratory diseases [9][10][11]. The public health system is currently the main concern for the global governance majority, receiving huge money investments and boosting researches in operational areas.…”
Section: Introductionmentioning
confidence: 99%